Potentials and challenges of bio-composites materials as engineering structures in ecological slope protection: a review - Mingyu, Sun; Mohd Khairul Azhar Mat Sulaiman,; Wardah Fatimah Mohammad Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Ecological slope protection technology has gained popularity as a sustainable and eco-friendly approach for slope restoration and conservation. The integration of ecological considerations into slope protection techniques has resulted in more sustainable and environmentally friendly solutions. In order to advance the development of ecological self-cycling, this study conducts a comprehensive review of the latest advancements in ecological slope protection technology materials. A systematic literature search was conducted using four databases (Web of Science, Scopus, Science Direct, and Google Scholar) and based on the keywords: ecological slope protection; slope protection; bio-composite material; bio-material; eco-material; eco-friendly building material; mycelium based material; natural fiber composite and biochar. This article provides a detailed discussion of the fundamental types of ecological slope conservation and the properties of materials used in ecological slope protection technology. The usage of environmentally friendly innovative materials has overtaken traditional engineered structures as the primary mode of ecological slope protection innovation. In particular, this study focuses on the structural basis of ecological slope protection, conducting a comparative analysis of the properties of existing bio-composites and evaluating whether they could replace the base structure of ecological slope protection. The findings of this study will contribute to the development of more sustainable and effective ecological slope protection techniques, thereby promoting ecological conservation and restoration.